Reconversion économique et persistance rituelle dans la communauté zapotèque de Mitla - Landon, Thérèse (Culture, 1993)
Every year, more than 200,000 tourists are visiting the archeological site of Mitla, located in Oaxaca state (Mexico). The Mitlena Zapotec community (8,500 people) has reacted to the waves of tourism by transforming its economy and developing the production and commercialization of artefacts. The economic impact of this new trade could have had dire consequences for the social fabric of Mitla, had the inhabitants privileged individual wealth over community life and reciprocity that used to be expressed during religious celebrations. Contrary to the predications, mitlenos have reaffirmed their communitarian identity, particularly at the time of marriage ceremonies to which are invited members of various community networks such as kinship and guelaguetza.